2004
DOI: 10.1111/j.1471-0528.2004.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in a series of cases of obstetric cholestasis identified via a patient support group

Abstract: aObjective To explore the clinical features of obstetric cholestasis pregnancies in UK white Caucasians.Design A questionnaire survey.Setting Study coordinated at Queen Charlotte's Hospital.Population Clinical features of 352 affected pregnancies in 227 Caucasian women identified via a patient support group. Methods Evaluation of the gestation at which prematurity and intrauterine death occur, and recording of additional clinical features in pregnancies complicated by obstetric cholestasis. Main outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
135
2
22

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(163 citation statements)
references
References 29 publications
4
135
2
22
Order By: Relevance
“…In addition, administration of oral micronized natural progesterone for prophylaxis of preterm labor causes increased rates of ICP (12). Moreover, there is experimental evidence demonstrating that cholestatic reproductive hormone metabolites can influence the major and minor bile acid uptake transporters, the sodium-dependent Na ϩ -taurocholate co-transporting polypeptide (NTCP), and the Na ϩ -independent organic anion transporting proteins (13,14), respectively, as well as the major canalicular bile salt export pump (BSEP) (14 - 4 The abbreviations used are: ICP, intrahepatic cholestasis of pregnancy; P4-S, sulfated progesterone metabolite; PHH, primary human hepatocyte; TC, taurocholate; PM4-S, allopregnanolone-sulfate; PM5-S, epiallopregnanolone-sulfate; NTCP, Na ϩ -taurocholate co-transporting polypeptide; GC-MS, gas chromatography-mass spectrometry; HPLC, high pressure liquid chromatography; MS/MS, tandem mass spectrometry; BSEP, bile salt export pump. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, administration of oral micronized natural progesterone for prophylaxis of preterm labor causes increased rates of ICP (12). Moreover, there is experimental evidence demonstrating that cholestatic reproductive hormone metabolites can influence the major and minor bile acid uptake transporters, the sodium-dependent Na ϩ -taurocholate co-transporting polypeptide (NTCP), and the Na ϩ -independent organic anion transporting proteins (13,14), respectively, as well as the major canalicular bile salt export pump (BSEP) (14 - 4 The abbreviations used are: ICP, intrahepatic cholestasis of pregnancy; P4-S, sulfated progesterone metabolite; PHH, primary human hepatocyte; TC, taurocholate; PM4-S, allopregnanolone-sulfate; PM5-S, epiallopregnanolone-sulfate; NTCP, Na ϩ -taurocholate co-transporting polypeptide; GC-MS, gas chromatography-mass spectrometry; HPLC, high pressure liquid chromatography; MS/MS, tandem mass spectrometry; BSEP, bile salt export pump. …”
mentioning
confidence: 99%
“…Approximately 25% of women with asymptomatic hypercholanemia of pregnancy subsequently develop intrahepatic cholestasis of pregnancy (ICP), 4 a liver disorder that presents with pruritus, raised serum bile acids, and liver transaminases (3). In pregnancies complicated by maternal serum bile acid levels of Ͼ40 M, there are increased rates of spontaneous preterm labor, fetal asphyxial events, and meconium-stained amniotic fluid (3).…”
mentioning
confidence: 99%
“…1 For the mother the disease is usually transient and resolves rapidly following delivery, but the condition is associated with spontaneous preterm labour, meconium-stained amniotic fluid and fetal asphyxial events, 1 -6 all of which have been reported to occur more commonly in pregnancies where the maternal fasting serum bile acid levels are greater than 40 mmol/L. 4,5,7 Unexplained intrauterine fetal death is thought to occur more commonly at later gestational weeks 1,8,9 and as a consequence many obstetricians deliver women with OC between 37 and 38 weeks gestation. 10 However, concerns over such 'active management' include the risk of failed induction and slow progress in the first or second stage of labour requiring operative delivery by caesarean section or instrumental assistance.…”
Section: Introductionmentioning
confidence: 99%
“…In the April issue of HEPATOLOGY, Marrero et al 1 reported that the Barcelona Clinic Liver Cancer (BCLC) "staging classification" provided the best prognostic stratification for patients with hepatocellular carcinoma (HCC). Their staging validation, however, is limited by critical shortcomings.…”
Section: Staging Of Hepatocellular Carcinomamentioning
confidence: 99%
“…A recent study by Williamson et al 1 investigated fetal outcome in women with ICP, and they reported high fetal complication rates. However, in this study several confounding factors were present.…”
mentioning
confidence: 99%